School of Computing Course Slots Distribution System - Ho Kai Xuan,; Aniza Mohamed Din, (Multidisciplinary Applied Research and Innovation, 2023)
Every year there will be thousands of students enrolling into universities. Before the starting of every semester, the head of department in all schools have a very important job which is deciding the numbers of classes/slots to be opened for every course and submit them to the Academic Affairs (HEA) office. The number of classes/slots for each course is determined based on the number of students enrolled for the course. Knowing the accurate number of classes/slots to be opened could help in allocating suitable lecture halls for each class/slot. This would then ensure the lecture halls are used to the fullest and the students would have a comfortable learning environment. The traditional method of counting the number of classes/slots manually course by course is rather troublesome and time consuming. Therefore, a web-based School of Computing (SOC) Course Slots Distribution System is developed to help solve the problem. The system aims to distribute the classes/slots for each course in BSc in Information Technology and BSc in Computer Science according to the number of students enrolled for the course. The system is developed using HTML, PHP and CSS. The system was then tested by the representatives of SOC management and evaluated based on user acceptance using an online survey platform – Google Form. The result of the evaluation suggested that the SOC Course Slots Distribution System is usable to assist the head of department of every school in Universiti Utara Malaysia (UUM) to calculate the number of classes/slots to be opened for each course efficiently. The respondents also suggested for the system to have lab allocation as well for further improvement.  With the help of this system, the workload of head of departments will greatly decrease.